Landasan Epistemologi Ilmu dan Aplikasinya dalam Pengembangan Ilmu Manajemen Islam - Turrohma, Mitra; Alwis, Dona Ana Yori; Ardimen, Ardimen (Indo-MathEdu Intellectuals Journal, 2024)
This article aims to explain the epistemology of science. The method used is library research in the form of references from various ready-to-use library data sources so that it can be used immediately and is not limited by space and time. The main data of articles comes from library data from various sources such as books, journals, articles, official websites, and other internet sources in the form of basic material to the main material about the nature of scientific epistemology. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the analysis show that epistemology is related to the way understanding and knowledge are obtained in the context of Islamic education. It includes sources of knowledge, methods of knowledge, and truth. By understanding the sources of knowledge, knowledge methods, and truths in Islamic education management, it is hoped that educational institutions can make a positive contribution in forming individuals who are knowledgeable, moral, and able to make a positive contribution to society and Muslims as a whole.